Legal Advisory About The Dangers Of Hoax News For Millenial Generations In Madrasah Aliyah Negeri I Probolinggo - Mushafi; Faridy (Fakultas Hukum, UPN Veteran Jawa Timur, 2020)
This community service is packed with legal counseling with the theme